Complement Interception Across Humoral Incompatibility in Solid Organ Transplantation : A Clinical Perspective - Biglarnia, Ali-Reza ; 0009-0004-2293-0740; Ekdahl, Kristina N; Nilsson, Bo (Advances in Experimental Medicine and Biology, 2015)
The humoral barrier in transplant biology is the result of preformed donor-specific antibodies (DSAs), directed either against human leukocyte antigens (HLA) or non-HLA antigens such as blood group (ABO) molecules. The term "sensitization" applies to patients carrying these antibodies. Transplantation is widely accepted as a life-saving opportunity for patients with terminal end-organ disease. However, in sensitized patients, transplant outcome is hampered by antibody-mediated rejection (AMR) as a consequence of DSA exposure. Furthermore, sensitized patients have limited access to "matched" organs from the both living and deceased donor pool.Considering the crucial role of the complement system in the pathophysiology of AMR and the availability of complement intervention therapeutics, there is a growing interest in complement-targeting strategies. This review highlights the emerging importance of monitoring and modulation of the complement system in the context of enabling transplantation across humoral incompatibility in sensitized recipients with preformed anti-HLA or natural anti-ABO antibodies. It also discusses the significance of the complement system in the induction of accommodation and further emphasizes current and future perspectives of novel complement therapeutics.
Keywords: ABO Blood-Group System/genetics; Antibodies, Monoclonal, Humanized/therapeutic use; Antibody Formation/drug effects; Blood Coagulation Factors/antagonists & inhibitors; Complement Activation/drug effects; Complement C1 Inhibitor Protein/therapeutic use; Complement Inactivating Agents/therapeutic use; Complement System Proteins/drug effects; Desensitization, Immunologic/methods; Gene Expression; Graft Rejection/immunology; HLA Antigens/genetics; Histocompatibility Testing; Humans; Immunity, Humoral/drug effects; Kidney Transplantation; Unrelated Donors